Abomasal tympanism due to sand impaction in neonate calf – case report (Research, Society and Development, 2021)
Abomasal diseases in newborn calves are infrequent, but when they occur they are associated with severe clinical manifestations, a poor prognosis, high cost of treatments, developmental delay and death. Among these diseases, abomasal tympanism stands out for its frequency and clinical severity. Aimed report a case of abomasal tympanism due to sand impaction in a 12-day-old heifer. The animal had a clinical history of frequent episodes of colic, loss of appetite, tachycardia, tachypnea, and abdominal distension with the presence of subtympanic resonance on percussion of the right paralumbar fossa; complementary exams were performed, such as blood count, which evidenced neutrophilic leukocytosis and hyperfibrinogenemia, analysis of the ruminal content, which revealed increase in the chloride content was found, and ultrasonography, whose images suggested marked abomasal distension in the right antimere; the animal was submitted to exploratory laparotomy, and abomasal tympanism secondary to sand impaction was diagnosed, which was corrected through abomasotomy and subsequent emptying of the organ. The clinical evolution of the animal was satisfactory, with return of the physiological clinical parameters, followed by hospital discharge on the third day of hospitalization. The unique aspects of this case are highlighted, whereby the calf was not fed artificially and the presence of about 1kg of sand in the abomasum from ingestion in an animal only 12 days old. Therefore, it is suggested that sand impaction be included among the differential diagnoses of abomasopathies in newborn calves, particularly if predisposing factors for excessive intake of sand are observed.